Pengaruh EDO (Edukasi Media Video) Terhadap Tingkat Pengetahuan Dan Sikap Ibu Menyusui Tentang Asi Eksklusif Di Wilayah Puskesmas Gunung Pati Semarang - Mei Indah Epiphani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: The percentage of coverage for babies aged 0–6 months who receive exclusive breastfeeding at the Gunung Pati Health Centre in Semarang is 70.29%; this figure is still lower than the achievement of exclusive breastfeeding in Semarang City (71.9%). Providing education using the video method in the context of health education is considered more capable and effective in changing one's knowledge or attitude. The research aims to determine the effect of video media education on the knowledge and attitudes of breastfeeding mothers regarding exclusive breastfeeding at the Gunung Pati Community Health Centre, Semarang. Methodology: This quantitative study used a quasi-experimental research design using a one-group pre-test-post-test design. The research was conducted in July 2023. The study population consisted of 53 mothers breastfeeding babies aged 0–3 months, and using the Solin formula, a total sample of 37 respondents was obtained. The intervention was carried out by giving a video (5 minutes in duration) and was carried out two times, 1 week apart. Data analysis used univariate and bivariate analysis (paired sample t test). Results: The average score on knowledge before and after the intervention has increased by 12.38. While the average score on attitudes before and after being given the intervention increased by 19.46, The statistical test showed that the provision of education using video media had an effect on the level of knowledge and attitudes of mothers about exclusive breastfeeding (p-value = 0.001, namely < 0.05), so that it could be said that Ha was accepted and Ho was rejected. Conclusion: There is an influence of EDO (video media education) on mothers' knowledge and attitudes about exclusive breastfeeding. So that the provision of education using video media is important and useful for breastfeeding mothers to increase the coverage of exclusive breastfeeding.